Teen fit future: engaging adolescents in the fight against obesity - Azmi, Muhammad Fairuz; Reza Huzairi, Ziqry Huzairy; Emile Mazlan, Muhammad Farish; Shahrul Azmi, Muhammad ‘Irfan Isyraf; Mohd Ariffin, Muhammad Afzani Imran; Saupi, Amjad Safwan; Fahmi Zamir, Muhammad Arif; Ishak, Nor Fatimah (Faculty of Medicine, 2025)
A dolescent obesity continues to rise in Malaysia, reflecting global trends and signalling a growing public health challenge. With nearly one in three Malaysian teenagers now classified as overweight or obese, early intervention has become more crucial than ever 1. Recognising this urgent need, a team of Year 2 medical students from the Faculty of Medicine, UiTM conducted an impactful awareness programme titled Teen Fit Future: Tackling Obesity Head-On at Asia Pacific Smart School Secondary, Subang Jaya.